Monitoring Power Consumption On LED Using LED Matrix P10 Panel - Prasetyo Yuliantoro; Shinta Romadhona; Deva Ourelia Ayuninda (Politeknik Negeri Semarang, 2023)
Information media is an essential medium in communication. So that the information provided is easy to see and read, the media used is placed in a visible place. Nowadays, data has become an inseparable part of process performance. With the advancement of technology, many new information media use electronic media that is used not only as news and advertising media but also as information media located in buildings or offices. Display running text matrix can be used to make the text according to the desired character. Besides, all Work and human needs are highly dependent on electrical energy. Human negligence in using electrical energy will cause waste, which also impacts the cost of using electrical energy. Therefore, we need a tool that can monitor the consumption of electrical power and limit the current use of the load, even if the user of electrical energy is not in place. Of course, making this tool requires a voltage sensor, sensor current ACS712, Arduino nano, and NodeMCU. This tool will monitor the power IoT-based and can be monitored via the internet as a graphical display on the server thingspeak.com. The results of this design can measure voltage one and voltage sensor two with an average error value of 1.75% and 1.38%, and the current measurement has an error value between 0.22% to 3.82% with an average error value of 1.46%.